{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

Lect_16 - Nonlinear Systems and Control Lecture 16 Feedback...

Info iconThis preview shows pages 1–6. Sign up to view the full content.

View Full Document Right Arrow Icon
Nonlinear Systems and Control Lecture # 16 Feedback Systems: Passivity Theorems – p.1/22
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full Document Right Arrow Icon
a aA ±² a a A aA ±² A A ± ² u 1 u 2 e 1 e 2 y 1 y 2 H 1 H 2 + + + ˙ x i = f i ( x i ,e i ) , y i = h i ( x i ,e i ) y i = h i ( t,e i ) – p.2/22
Background image of page 2
Passivity Theorems Theorem 6.1: The feedback connection of two passive systems is passive Prove using V = V 1 + V 2 as a Lyapunov func. candidate Proof: Let V 1 ( x 1 ) and V 2 ( x 2 ) be the storage functions for H 1 and H 2 , respectively. If H i is memoryless, then take V i = 0 . Since H i is passive, we have e T i y i ˙ V i From the feedback connection, e T 1 y 1 + e T 2 y 2 = ( u 1 y 2 ) T y 1 +( u 2 + y 1 ) T y 2 = u T 1 y 1 + u T 2 y 2 u T y = u T 1 y 1 + u T 2 y 2 ˙ V 1 + ˙ V 2 = ˙ V – p.3/22
Background image of page 3

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full Document Right Arrow Icon
Theorem 6.3: Consider the feedback connection of two dynamical systems. When u = 0 , the origin of the closed-loop system is asymptotically stable if each feedback component is either strictly passive , or output strictly passive and zero-state observable Furthermore, if the storage function for each component is radially unbounded, the origin is globally asymptotically stable Proof: H 1 is SP; H 2 e T 1 y 1 ˙ V 1 + ψ 1 ( x 1 ) , ψ 1 ( x 1 ) > 0 , x 1 n = 0 e T 2 y 2 ˙ V 2 + y T 2 ρ 2 ( y 2 ) , y T 2 ρ ( y 2 ) > 0 , y 2 n = 0 – p.4/22
Background image of page 4
e T 1 y 1 + e T 2 y 2 = ( u 1 y 2 ) T y 1 +( u 2 + y 1 ) T y 2 = u T 1 y 1 + u T 2 y 2 V ( x ) = V 1 ( x 1 ) + V 2 ( x 2 ) ˙ V u T y ψ 1 ( x 1 ) y T 2 ρ 2 ( y 2 ) u = 0 ˙ V ≤ − ψ 1 ( x 1 ) y T 2 ρ 2 ( y 2 ) ˙ V = 0 x 1 = 0 and y 2 = 0 y 2 ( t ) 0 e 1 ( t ) 0 x 1 ( t ) 0 )
Background image of page 5

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full Document Right Arrow Icon
Image of page 6
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

Page1 / 22

Lect_16 - Nonlinear Systems and Control Lecture 16 Feedback...

This preview shows document pages 1 - 6. Sign up to view the full document.

View Full Document Right Arrow Icon bookmark
Ask a homework question - tutors are online